A Practical and Versatile Method for the C–H Sulfenylation of Imidazo[1,2-a]pyridines - Al-Saedy, Muhannad A. E.; Harrity, Joseph P. A. (Synlett, 2020)
Imidazo[1,2-a]pyridines are an important class of heterocycles that are prevalent in many bioactive small molecules. We report the direct introduction of a broad selection of aromatic, heteroaromatic, or alkyl fragments connected by a thioether group into these important heterocycles by using readily prepared thiosulfate salts.
Keywords: imidazopyridines; coupling reaction; C–H functionalization; thioethers; regioselectivity; sulfenylation